Druggable proteins of Alistipes reveal promising antimicrobial targets against chronic intestinal inflammation - Sohail, Saman; Wisal, Ayesha; Rana, Sobia; Abid Khan, Rao Muhammad; Ullah, Asad; Khan, Farooq-Ahmad; Irfan, Muhammad; Imran, Muhammad; Carvalho, Paulo V. S. D.; Rozental, Renato; Shaheen, Farzana; Hassan, Syed Shah (Frontiers in Pharmacology, 2025)
IntroductionThe genus Alistipes consists of anaerobic, Gram-negative bacteria with 13 species that colonize the entire gastrointestinal tract and are a serious health concern. They contribute to gut dysbiosis, intestinal inflammation, colorectal cancer, and depression.MethodsTo explore potential therapeutic targets and inhibitors, we filtered the core genome of Alistipes strains through subtractive genomics for non-host homology, gene essentiality, PPI, KEGG pathways, virulence, cellular localization, and druggability. The potential targets were docked against two drug-like libraries (ZINC, n = 11,993) and TCM (n = 36,043). ADMET profiling for best hits and MD simulation for apo/complex structures were performed, followed by physicochemical and pharmacokinetic evaluation and complex stabilities.Results and DiscussionA set of 39 potential proteins was drastically reduced to only two targets after sequential data mining. The 3D structures of the selected targets (LpxA and KdsB) revealed good druggability scores. The top hits (ZINC85530940, ZINC05161112, ZINC95911713, and ZINC05566415) for both targets showed maximum H-bond interactions. The RMSD and RMSF values exhibited compactness with minimum fluctuation in ligand-bound complexes. The β-factor of ZINC05161112 at 327th residue and 352nd residue exhibited higher thermal instability, consistent with the RMSF results. The globularity of the complexes and apo structures remained consistent, whereas the LpxA complexes exhibited lower solvent-accessible surface area. For the KdsB, the surface area for ZINC5566415 increased significantly, with a steep decrease for ZINC95911713, establishing rather stable protein-ligand complexes. The results highlight the importance of identifying novel inhibitors and therapeutic targets. They are crucial for establishing better treatment regimes for human health and to aid in controlling the pathogenicity of Alistipes species.